Politics and the Imagination - Geuss, Raymond (Book collections on Project MUSE., 2010)
In politics, utopians do not have a monopoly on imagination. Even the most conservative defenses of the status quo, Raymond Geuss argues, require imaginative acts of some kind. In this collection of recent essays, including his most overtly political writing yet, Geuss explores the role of imagination in politics, particularly how imaginative constructs interact with political reality. He uses decisions about the war in Iraq to explore the peculiar ways in which politicians can be deluded and citizens can misunderstand their leaders. He also examines critically what he sees as one of the most.